Paradigm Shift in Islamic Mutual Fund Research: Bibliometric Analysis from Conventional to Digital Era - Siti Hasmah Dita Sp; Taufiqur Rahman (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the paradigm shift in academic studies related to Islamic mutual funds, from the conventional to the digital era, using a bibliometric approach. Utilizing publication data from the Google Scholar database over the past five years (2020-2025), we analyzed publication trends, keywords, author collaborations, and changes in thematic focus. The analysis results show a significant increase in the number of publications since 2020, in line with the development of the Islamic finance and financial technology (fintech) industries. In the early era, research focused primarily on legal aspects, Islamic principles, and conventional financial performance, while in the last decade there has been a shift toward digital integration, such as the use of big data, artificial intelligence, and digital applications in Islamic mutual fund management. These findings reflect the changing scientific approach and the need for interdisciplinary integration between Islamic finance and digital technology. This research contributes to the understanding of the development of Islamic finance and opens opportunities for further research on the development of the digital ecosystem for Islamic mutual funds.